Introduction to Pasture-Raised Poultry: Maximizing Foraging Behavior - Brad Burbaugh; Elena Toro; Abel Gernat (EDIS)
AN237, a 5-page illustrated fact sheet by Brad Burbaugh, Elena Toro, and Abel Gernat, discusses foraging behavior, pasture management, pasture rotation, and other benefits of foraging. Includes references. Published by the UF Department of Animal Science, April 2010.